Undang-Undang Pesantren: Meneropong Arah Kebijakan Pendidikan Pesantren di Indonesia - Muhammad Usman; Anton Widyanto (Ar-Raniry: International Journal of Islamic Studies, 2021)
The ratification of Law Number 18 of 2019 concerning Islamic Boarding Schools on September 24, 2019, has given a new color and direction for implementing Islamic education in Indonesia. History has carved out the significant contribution of pesantren, both taking part in repelling colonialism and educating generations of the nation, even pesantren as the oldest educational institution in Indonesia. So far, the regulation of Islamic boarding schools has only been a small part of Law Number 20 of 2003 concerning the National Education System, and its speed only supports Government Regulation Number 55 of 2007 concerning Religious Education and Religious Education. These two legal policies still make pesantren unable to develop like other public education. The Law on Islamic Boarding Schools; making the existence of Islamic boarding schools stronger legally and impacts the state's obligation to be present in helping the pace of its development. This research was conducted with an analytical study model with a qualitative approach. The study results indicate that the pesantren institution is still maintained as full ownership in a private framework. Pesantren has three functions; education, propaganda, and community empowerment. Pesantren are also entitled to receive allocations of funds from the central and local governments. In the future, Islamic boarding schools also have quality assurance institutions, and education levels will be held up to doctoral levels. Nine derivative rules need to be immediately made by the central government so that the Pesantren Law can be implemented properly.